Nizp1 is a specific NUP98‐NSD1 functional interactor that regulates NUP98‐NSD1‐dependent oncogenic programs. (30th October 2022) - Berardi, Andrea; Botrugno, Oronza A.; Quilici, Giacomo; Manteiga, José Manuel Garcia; Bachi, Angela; Tonon, Giovanni; Musco, Giovanna
Abstract : NSD1, NSD2 and NSD3 proteins constitute a family of histone 3 lysine 36 (H3K36) methyltransferases with similar domain architecture, but diversified activities, in part, dependent on their non‐enzymatic domains. These domains, despite their high sequence identity, recruit the hosting proteins to different chromatin regions through the recognition of diverse epigenetic marks and/or associations to distinct interactors. In this sense, the PHDvC5HCH finger tandem domain represents a paradigmatic example of functional divergence within the NSD family. In this work, we prove and give a structural rationale for the uniqueness of the PHDvC5HCH domain of NSD1 in recognizing the C2HR Zinc finger domain of Nizp1 (NSD1 interacting Zn finger protein). Importantly, we show that, in a leukaemogenic context, Nizp1 is pivotal in driving the unscheduled expression of HoxA genes and of genes involved in the type I IFN pathway, triggered by the expression of the fusion protein NUP98‐NSD1. These data provide the first insight into the pathophysiological relevance of the Nizp1‐NSD1 functional association. Targeting of this interaction might open new therapeutic windows to inhibit the NUP98‐NSD1 oncogenic properties. Abstract : We prove and give a structural rationale for the uniqueness of the interaction between the PHDvC5HCH domain of the histone metyl transferase NSD1 and the C2HR Zinc finger domain of Nizp1 (NSD1 interacting Zn finger protein). We also show that in a leukaemogenic context, Nizp1 is pivotal in driving the unscheduled expression of HoxA genes, triggered by the expression of the fusion protein NUP98‐NSD1.